STATUS KELENGKAPAN IMUNISASI HEPATITIS B PADA USIA 0-6 BULAN DENGAN KEJADIAN HEPATITIS B - Lidia Widia (Jurnal Ilmiah Manuntung, 2017)
Immunization is a process to make the body's immune defense system against invading microorganisms (bacteria and viruses) that can cause infections before these microorganisms have a chance to invade our bodies. Hepatitis B immunization is the immunization to prevent the body less susceptible to hepatitis B virus. The purpose of this study was to identify whether there is the Relationship Between Hepatitis B Immunization Status Completed At Age 0-6 Month With Events Hepatitis B in the Work Area Puskesmas Perawatan Simpang Empat Kecamatan Simpang Empat Kabupaten Tanah Bumbu.This research method is analytical survey and cross sectional approach for studying the dynamics of the correlation between risk factors and the effects of the approach, observation or data collection at once at a time (point time approach), the sampling technique is taken with total sampling technique that met the inclusion criteria and exclusion of mothers with babies were recorded in the register Puskesmas Simpang Empat Kecamatan Simpang Empat Kabupaten Tanah Bumbu. The data obtained were analyzed using chi-square test with significance of 0.05. Chi-Square test results obtained there is a significant relationship between the completeness status of hepatitis B immunization (P = 0.005) with the occurrence of Hepatitis B, for the conclusion in this study found no relationship between the completeness status of hepatitis B immunization with Hepatitis B in Puskesmas Simpang Empat Kecamatan Simpang Empat Kabupaten Tanah Bumbu. It is hoped that no more infants are immunized against the completeness of incomplete hepatitis B immunization to reduce the incidence of hepatitis and reduce infant mortality